The Effect of Health Coaching-based Health Belief Model on Preventing the Pulmonary Tuberculosis Transmission at Puskesmas Karang Taliwang and Ampenan West Nusa Tenggara - Dady zharfan hanif; Muhammad Amin Amin; Andri Setiya Wahyudi; Nursalam Nursalam (Alta Dharma Publisher, 2020)
Adherence is an essential factor in achieving optimal health status in patients with tuberculosis. The study aimed to examine the effect of health coaching on preventing the infection of pulmonary tuberculosis patients. A quasi-experimental study design, pre, and post-test with the non-equivalent control group. Seventy samples were recruited by using a purposive sampling technique. The intervention group received the health coaching program for two months, while the control group received the usual care. The results showed that health coaching was to improve adherence prevention of infection (p<0,001). Health coaching based on the Health Belief Model was a positive effect on preventing infection transmission